Process tomography and instrumentation.Series 4 - Herlina Abdul Rahim, 1973-; Herlina Abdul Rahim, 1973-, author; Shafisuhaza Sahlan author; Ruzairi Abdul Rahim author; Mohd. Hafiz Fazalul Rahiman, 1981-, author; Jaysuman Pusppanathan author; Zulkarnay Zakaria, 1976-, author; Nur Farahiyah Mohamad author; Mohd. Hafiz Hussin author; Salinda Buyamin author; Norhaliza Abd. Wahab author; Effendi Awang author; et al. (Skudai : Penerbit Universiti Teknologi Malaysia, 2011)
Includes bibliographical references and index